2011
DOI: 10.2214/ajr.10.6102
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Exposure for Lumbar Spine Epidural Steroid Injections: A Comparison of Conventional Fluoroscopy Data and CT Fluoroscopy Techniques

Abstract: The ED for the CTF-guided ESI was almost half that of conventional fluoroscopy because of the shorter fluoroscopy time. However, the overall radiation dose for CTF-guided ESIs can be up to four times higher when a full diagnostic lumbar CT scan is performed as part of the procedure. Radiation dose reduction for CTF-guided ESI is best achieved by minimizing the dose from the preliminary planning lumbar spine CT scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 13 publications
0
34
1
Order By: Relevance
“…However, the increase in effective dose caused by the need for a spiral CT scan for better localization of the cervical nerve root and planning of the access was lower for the cervical spine than for the lumbar spine. Although such a scan was necessary in 17 of 64 cases in our study and the average effective dose of 0.85 mSv was significantly higher, the increase in the study of Hoang et al [39] was up to 2.9 mSv for the lumbar spine. Since MRI-guided nerve root infiltration does not require radiation exposure for patients and personnel, it should be used primarily in patients with expected severe degenerative changes of the cervical spine, in the case of an anticipated serial therapy regimen, and in younger patients.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…However, the increase in effective dose caused by the need for a spiral CT scan for better localization of the cervical nerve root and planning of the access was lower for the cervical spine than for the lumbar spine. Although such a scan was necessary in 17 of 64 cases in our study and the average effective dose of 0.85 mSv was significantly higher, the increase in the study of Hoang et al [39] was up to 2.9 mSv for the lumbar spine. Since MRI-guided nerve root infiltration does not require radiation exposure for patients and personnel, it should be used primarily in patients with expected severe degenerative changes of the cervical spine, in the case of an anticipated serial therapy regimen, and in younger patients.…”
Section: Discussioncontrasting
confidence: 52%
“…The radiation exposure needed for CT fluoroscopic guidance has a potentially damaging effect on patients and personnel [15 -17] and is of importance because many patients often require multiple interventions to achieve lasting pain relief. Hoang et al [39] and Schmid et al [40] documented the average effective dose in CT-guided nerve root infiltrations with the help of a phantom model and calculated average effective dose values of 0.45 mSv and between 0.22 -0.45 mSv. A similar average dose value of 0.48 mSv (approximated) was achieved in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of our study, we recommend a tube current of 40 mA or less for a body AP diameter of Յ30 cm. This technique of stratifying patients by body size could also be used for selecting tube current for the planning CT, as prior studies have shown that the greatest contributor to dose for CT-guided lumbar injections is the planning CT. 5 There are several limitations to this study. First, this is a retrospective study of a small number of patients at a single academic institution.…”
Section: Discussionmentioning
confidence: 94%
“…In the lumbar spine, CT guidance offers advantages over conventional fluoroscopy of improved soft tissue resolution, 1 improved precision in needle placement, 2,3 and decreased procedure time. 4,5 However, because of the higher tube current for CT compared with conventional fluoroscopy, when possible, proceduralists need to be mindful of radiation dose optimization and minimize dose.…”
mentioning
confidence: 99%
See 1 more Smart Citation